Investigation of intermediate cooling capacity from a single-stage coaxial pulse tube cryocooler. (25th November 2022) - Han, Yinan; Zhang, Ankuo; Yu, Wenhui; Xiong, Chao
Highlights: The effect of inter-cooling capacity from a single-stage coaxial PTC is investigated. Inter-cooling capacity effects on the enthalpy flow, phase and losses are analyzed. The single-stage PTC can achieve cooling powers of 4 W@70.7 K and 4 W@237.7 K. Abstract: Pulse tube cryocoolers (PTCs) are suitable for cooling infrared detectors in space. With the development of multi-spectral detection, multi-temperature cooling of PTCs is essential. Multi-stage and two cold finger coolers are commonly used, which are not compact and difficult to control. To further compactness, we investigate the intermediate cooling capacity of a single-stage coaxial PTC in this paper. The single-stage PTC achieves dual temperature cooling by obtaining cooling power simultaneously from the cold end and the middle of its cold finger. Based on theoretical and simulation analysis, the effects of inter-cooling power on the temperature variation, loss, and phase angle, and the cooling performance at the dual-temperature zone with different input power are derived. Additionally, some experiments are carried out to demonstrate the accuracy of the theory and simulation, and the reasons for the difference between the simulation and the experiment are explained. The experiment shows that the cooling temperature of the cold end can increase from 70.7 K to 87.4 K when the inter-cooling capacity increase from 1 W to 4 W with an input power of 150 W and a cooling capacity of 4 W.